Neuropsychological function in obsessive-compulsive disorder: effects of comorbid conditions on task performance - Aycicegi, Ayse; Dinn, Wayne M; Harris, Catherine L; Erkmen, Husnu (European psychiatry, 2003)
Background. – Neuropsychological testing reveals a pattern of impairment among patients with obsessive-compulsive disorder (OCD) which implicates the orbitofrontal region. Studies of neuropsychological function in OCD differ regarding performance deficits on classical tests of frontal executive function. In some studies, OCD patients did not demonstrate impaired performance on tests of executive function. However, other researchers have documented performance deficits among OCD patients on measures of executive function. Patients with OCD also exhibit performance deficits on tests of visual/spatial memory and verbal memory. Again, in some studies, OCD patients did not demonstrate impaired performance on tests of memory function. How can we account for the conflicting findings? One possibility is that performance deficits on tests of cognitive function are associated with comorbid conditions. In prior work, we observed that OCD patients who did poorly on executive function tasks obtained high scores on a measure of schizotypal personality. A second possibility is that executive function deficits among patients with OCD are associated with comorbid depressive symptoms. Method. – In the present study, a comprehensive neuropsychological test battery was administered to patients with OCD and matched healthy control subjects. We also administered dimensional measures of schizotypal personality and depression to patients with OCD and controls. We conducted analyses of covariance (ANCOVA), with scores on measures of schizotypal personality and depression used as covariates. Results. – OCD patients demonstrated performance deficits on measures of delayed memory, response inhibition, alternation learning, and obtained significantly higher scores on measures of disinhibition, impulsivity, and temporolimbic symptoms; however, OCD patients did not exhibit impaired performance on tests of executive function and verbal fluency, and did not report a significantly greater number of dysexecutive symptoms, when coexistent depressive and schizotypal symptoms were taken into account. Conclusion. – Findings are consistent with the contention that dysfunction of an orbitofrontal-limbic network underlies OCD.